TINDAK TUTUR TOKOH KOBAYASHI SENSEI DALAM ANIME MADOGIWA NO TOTTO-CHAN - Qeysha Nabila Satiyaatmaja; Ni Putu Candra Lestari; Ni Putu Luhur Wedayanti (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2026)
This study aims to identify the types of illocutionary and perlocutionary acts, elucidate the components of speech situations, and analyze the linguistic politeness factors exhibited by the character Kobayashi Sensei in the anime Madogiwa no Totto-chan (2023). Employing a qualitative approach grounded in content analysis, the research examines a dataset consisting of 17 data entries comprising 45 utterances by Kobayashi Sensei, which were gathered through observational methods and note-taking techniques. The theoretical framework of this study integrates Austin and Searle’s (1969) speech act and speech situation theories, complemented by Mizutani and Mizutani’s (1987) linguistic politeness theory. The findings reveal that directive illocutionary acts constitute the most dominant category deployed by Kobayashi Sensei to foster active student participation. The employment of these speech acts yields a profound perlocutionary effect, instigating positive transformations such as bolstered student self-confidence and the cultivation of emotional proximity between educator and learners. Regarding linguistic politeness, the selection of utterances is heavily influenced by social relations, age, group membership and situational factors. These considerations are manifested through politeness strategies that emphasize togetherness, the utilization of backchannel signals (aizuchi), final particles, and indirectness strategies designed to preserve the interlocutors' face, ultimately forging a profound emotional bond between the teacher and students at Tomoe Gakuen.